Pencegahan Tindak Korupsi di dalam Lingkungan Perkantoran - Fikri Ardiansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Preventing acts of corruption in the office environment involves a series of strategic steps to create a culture of transparency and accountability. These efforts include implementing a code of ethics, training on integrity, and strict supervision of the decision-making process. In addition, the application of information technology to monitor financial transactions and reports can help detect potential fraud. By building awareness and commitment of all employees towards preventing corruption, organizations can increase public trust and create a healthier work environment. Preventing acts of corruption in the office environment is a crucial step in creating good governance and improving institutional integrity. Corruption can hinder economic growth and damage public trust. To prevent this, a comprehensive approach is needed, including implementing transparency policies, strengthening supervisory systems, and ethical education for employees. In addition, an organizational culture that supports openness and accountability must be built. This research discusses effective strategies that can be implemented to minimize the risk of corruption, including the use of information technology and participation in community oversight. The results are expected to provide recommendations for government and private agencies in strengthening efforts to prevent corruption